2017
DOI: 10.1155/2017/7819590
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Test Pattern Generator for Fuzzing Based on Finite State Machine

Abstract: With the rapid development of the Internet, several emerging technologies are adopted to construct fancy, interactive, and userfriendly websites. Among these technologies, HTML5 is a popular one and is widely used in establishing modern sites. However, the security issues in the new web technologies are also raised and are worthy of investigation. For vulnerability investigation, many previous studies used fuzzing and focused on generation-based approaches to produce test cases for fuzzing; however, these meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Besides context-free grammars, fuzzers have used alternate input specifications, such as regular languages (i.e. finite state automata) [9,43], or constraint languages [12]. MoWF [30] leverages a specification expressed as a constraint over the input space.…”
Section: Other Specification Languagesmentioning
confidence: 99%
“…Besides context-free grammars, fuzzers have used alternate input specifications, such as regular languages (i.e. finite state automata) [9,43], or constraint languages [12]. MoWF [30] leverages a specification expressed as a constraint over the input space.…”
Section: Other Specification Languagesmentioning
confidence: 99%
“…It has been shown that different fuzz techniques can find different types of bugs in the same software system [7]. There are some fuzzers that use finite state machines to model the software and apply fuzz tests to the model [8], [9]. This suggests that fuzz testing can be beneficial to a particular context, such as using state machines to define robotic behavior.…”
Section: Related Workmentioning
confidence: 99%